A consumer behavioural approach to food waste - Aktas, Emel; Sahin, Hafize; Topaloğlu, Zeynep; Oledinma, Akunna; Samsul Huda, Abul Kalam; Irani, Zahir; Sharif, Amir M.; van't Wout, Tamara; Kamrava, Mehran (Emerald, 2018)
Purpose Food waste occurs in every stage of the supply chain, but the value-added lost to waste is the highest when consumers waste food. The purpose of this paper is to understand the food waste behaviour of consumers to support policies for minimising food waste. Design/methodology/approach Using the theory of planned behaviour (TPB) as a theoretical lens, the authors design a questionnaire that incorporates contextual factors to explain food waste behaviour. The authors test two models: base (four constructs of TPB) and extended (four constructs of TPB plus six contextual factors). The authors build partial least squares structural equation models to test the hypotheses. Findings The data confirm significant relationships between food waste and contextual factors such as motives, financial attitudes, planning routines, food surplus, social relationships and Ramadan. Research limitations/implications The data comes from an agriculturally resource-constrained country: Qatar. Practical implications Food waste originating from various causes means more food should flow through the supply chains to reach consumers’ homes. Contextual factors identified in this work increase the explanatory power of the base model by 75 per cent. Social implications Changing eating habits during certain periods of the year and food surplus have a strong impact on food waste behaviour. Originality/value A country is considered to be food secure if it can provide its citizens with stable access to sufficient, safe and nutritious food. The findings and conclusions inform and impact upon the development of food waste and food security policies.
Keywords: Consumer behaviour; Structural equation modelling; Food waste